Trait emotional intelligence mediates the dispositional gratitude and subjective well-being in young adults - Torrelles-Nadal, Cristina; Ros-Morente, Agnès; Quesada-Pallarès, Carla (Frontiers in Psychology, 2024)
Gratitude has proved to be an enhancer of subjective well-being in previous studies. However, studies that linked the relation between emotional intelligence and its facets when interacting with gratitude, are still limited. In this sense, this study examined the mediating roles of emotional intelligence between gratitude and subjective well-being indicators, by introducing the general factor of emotional intelligence. The first approach to data analysis was to examine the descriptive statistics; the second approach consisted of an Exploratory Structural Equation Modelling, applying also a bifactor analysis. Data was collected from 406 Spanish students, through an online survey that includes the gratitude, trait meta mood scale, satisfaction with life and subjective happiness scale. The mean age of participants was 20.27 years (SD = 4.68), whereas 79.5% were females. The results provided preliminary evidence of the mediation role of the general factor of emotional intelligence between gratitude and subjective well-being, which provided a meaningful insight about the role of trait emotional intelligence. These findings suggested that gratitude promotes emotional intelligence, allowing to an increase in subjective well-being. Nonetheless, there is a need for further research to achieve a better understanding of the role of the emotional intelligence facets between gratitude and subjective well-being.